GAMBARAN PENGEMBALIAN DOKUMEN REKAM MEDIS RAWAT INAP RUANG VII TRIWULAN IV TAHUN 2013 DI RUMAH SAKIT UMUM DAERAH TASIKMALAYA - Ulfah Fauziah; Ida Sugiarti (Asosiasi Perguruan Tinggi Rekam Medis dan Informasi Kesehatan Indonesia- APTIRMIKI, 2014)
ABSTRACTThe purpose of the research is to know the plots of returning of medical recording document of hospitalizingat RSUD Tasikmalaya that is suitable with the SOP, to know the plots of returning the medical recordingdocument of hospitalizing at RSUD Tasikmalaya that is not suitable with SOP, to know the descriptionofreturning the medical recording unit which was late from room VII in 2013 at RSUD Tasikmalaya and to knowthe description of returning the medical recording document of hospitalizing from the ward to the medicalrecording unit which was on time from room VII in 2013 at RSUD Tasikmalaya.The kind of research is descriptive by retrospective approach, the method is gathering data observation.Population and sample of this research are 714 sample of medical recording document of hospitalizing at roomVII and about 256 sample of medical recording document at room VII by using random sampling technique.The data analysis is used univariate analysis.The result of the research shows that the returning of medical recording document of hospitalizing at roomVII with the higher percentages of the returning of medical recording unit on time is in October as much as78,82% from the 67 documents and higher percentage of the late returning of medical recording is in Decemberas much as 84,88% from the 73 the total of the documents.In general, the returning of medical recording document of hospitalizing at room VII is equal with the plots ofthe returning of medical recording document, the maximum time is used for the returning of medical recordingis about 14 days.The key words: The late of returning of medical recording document